2021
DOI: 10.1371/journal.pone.0253724
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the semi-slug Omalonyx unguis (Gastropoda: Succineidae) and the phylogenetic relationships within Stylommatophora

Abstract: Here we report the first complete mitochondrial genome of the semi-slug Omalonyx unguis (d’Orbigny, 1836) (Gastropoda: Succineidae). Sequencing was performed on a specimen from Argentina. Assembly was performed using Sanger data and Illumina next generation sequencing (NGS). The mitogenome was 13,984 bp in length and encoded the 37 typical Metazoan genes. A potential origin for mitochondrial DNA replication was found in a non-coding intergenic spacer (49 bp) located between cox3 and tRNA-Ile genes, and its sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 102 publications
3
6
0
Order By: Relevance
“…The secondary structure of the 12S rRNA of P. reevei ( Figure 6 ) and P. aulanieri ( Figure S3 ) had an identical organization of four structural domains, with Domain III as the most conserved region, allowing its successful PCR across a wide variety of taxa [ 48 ]. Here, we found that the structure of Domain III in P. reevei and P. aulanieri is similar to previous reports in other mollusks [ 27 , 49 , 50 , 51 ]. On the other hand, Domains I and II have been poorly studied and they were difficult to infer in both species.…”
Section: Resultssupporting
confidence: 91%
“…The secondary structure of the 12S rRNA of P. reevei ( Figure 6 ) and P. aulanieri ( Figure S3 ) had an identical organization of four structural domains, with Domain III as the most conserved region, allowing its successful PCR across a wide variety of taxa [ 48 ]. Here, we found that the structure of Domain III in P. reevei and P. aulanieri is similar to previous reports in other mollusks [ 27 , 49 , 50 , 51 ]. On the other hand, Domains I and II have been poorly studied and they were difficult to infer in both species.…”
Section: Resultssupporting
confidence: 91%
“…Our results are in accordance with that most PCGs use ATN as start codon in metazoan [10]. TTG is usually used as start codon for cox1 in animals [30,31]. Eight PCGs used TA (nad3 and nad6) or T (cox1, cox2, cox3, cytb, nad1, and nad2) as incomplete stop codon.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the mitochondrial genome is more suitable for distinguishing species with closer genetic relationships and exploring the evolutionary events within a short period of time. It has been widely applied for the study of taxonomy, population genetics, gene flow, interspecific molecular evolution and biogeography (Guzmán et al., 2021; Kong et al., 2020; Xu et al., 2021). In addition, the mitochondrial genome has been found to regulate the fermentation process of microorganisms.…”
Section: Introductionmentioning
confidence: 99%